TONGKONAN AS AN EDUCATIONAL CENTER FOR INTRODUCING FINANCIAL LITERACY TO BUILD AWARENESS OF SAVING FROM AN EARLY AGE IN LEMBANG LANGDA: TONGKONAN SEBAGAI PUSAT EDUKASI PENGENALAN LITERASI KEUANGAN UNTUK MEMBANGUN KESADARAN MENABUNG SEJAK DINI DI LEMBANG LANGDA - Stefani Marina Palimbong; Rahma Gusmawati Tammu; Olivia Devi Y. Pompeng; Mince Batara; Randi Tangdialla (Yayasan Education and Social Center, 2022)
This activity aims to provide knowledge and understanding of financial literacy through saving, to foster an interest in saving from an early age so that children get used to saving, as well as to provide examples of how to make piggy bank creations from bamboo. This activity was carried out in the tongkonan using the method of delivering socialization material then carrying out questions and answers, quizzes, and creatively making piggy banks from bamboo. From observations made in the field it was found that there was a lack of attention from parents in guiding children to learn to save from an early age. The results of this activity show change that have occurred in children such as children becoming interested in saving and some of them have started saving